2011
DOI: 10.1128/jb.06143-11
|View full text |Cite
|
Sign up to set email alerts
|

Roles of DNA Sequence and Sigma A Factor in Transcription of the vraSR Operon

Abstract: Cell wall damage in Staphylococcus aureus induces a rapid genome-wide response, referred to as the cell wall stress stimulon. This response is mediated by a two-component system, the vancomycin resistance-associated sensor/regulator (VraSR). The response regulator protein VraR is a transcription factor. Here, we demonstrate that two VraR binding sites in the vraSR operon control region are involved in the regulation of the vraSR operon. The sites are centered at the ؊60 and ؊35 nucleotide positions and are ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 35 publications
2
23
0
2
Order By: Relevance
“…Briefly explained, given our knowledge of the HK/RR paradigm (41), our data, and data from other published studies, cell wall damage first imparts a modification of VraT which in turn influences autophosphorylation of VraS, ultimately leading to the phosphorylation of VraR. VraR then activates or represses genes through binding to target promoters (23,24,42). Recent data demonstrating that portions of VraS and VraT interact in vivo support this idea (28).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Briefly explained, given our knowledge of the HK/RR paradigm (41), our data, and data from other published studies, cell wall damage first imparts a modification of VraT which in turn influences autophosphorylation of VraS, ultimately leading to the phosphorylation of VraR. VraR then activates or represses genes through binding to target promoters (23,24,42). Recent data demonstrating that portions of VraS and VraT interact in vivo support this idea (28).…”
Section: Discussionmentioning
confidence: 78%
“…VraS responds to antimicrobial-elicited cell wall stress by autophosphorylation and subsequent transphosphorylation of VraR, its cognate RR (23). Phosphorylated VraR binds to its own promoter and presumably to genes in the vra stimulon to activate or repress their transcription (24). It is known that cell wall stress is required, but the specific molecular signal responsible for induction of activation of VraS and VraR is still unknown.…”
mentioning
confidence: 99%
“…Both S. aureus σ A and E . coli σ 70 RNA polymerase subunits recognize canonical promoters and are interchangeable (49). It has already been reported that srn_9340 transcription depends on σ A (46).…”
Section: Resultsmentioning
confidence: 99%
“…It is puzzling however that Efm LiaR W73C does not actually confer the same extent of dimerization as BeF 3 − stimulated wild type Efm LiaR (wild type Efm LiaR dimerization K d was 15 μM compared to 236 μM for Efm LiaR W73C ). Since in vivo concentrations of LiaR are estimated to be in the low micromolar range [37], the weak in vitro dimerization of Efm LiaR W73C is less than expected for constitutive hyperactivation. Alternatively, the Efm LiaR W73C mutant may interact more efficiently with its cognate kinase LiaS to produce a higher extent of phosphorylation than the comparable wild type LiaR interaction with LiaS.…”
Section: Discussionmentioning
confidence: 99%